Trastorno de déficit de atención hiperactividad (TDAH) y su incidencia en el proceso de aprendizaje en los niños y niños de 8 años de edad en la Unidad Educativa Jesús Martinez de Ezquerecocha - Torres Guerrero, Shirley Marisol (2020)
Education in is a primary basis in each of the stages of life for the development of people and societies. At the childhood stage, they may present some undiagnosed psychological or psychiatric disorders that cause learning problems. Attention deficit syndrome is characterized by difficulty in maintaining attention and concentration. This work is intended to identify what is the incidence of attention deficit syndrome in children 7 to 8 years in school 18 November, what are the main factors influencing the presence of the syndrome, and what is the relationship with the performance Academic. The research is qualitative, quantitative, descriptive and transversal. The number of cases is 63 children corresponding to 26.25% between male and female gender, 73.02% is 7 years old, 26.98% are 8 years old. The factors influencing this syndrome have inadequate feeding with 39.68%; Also is sleep habit 44.44% sleep less than 8 hours, in addition the time dedicating for their activities 33.33% see television 63.49% it is greater than two hours a day and 44.44% see caricatures some that have a negative influence on the development of a child. Finally, 36.5% live with a single parent or other family member. As for the child's academic performance, 44.44% have a good performance.